Vibration Energy Harvesting from Plates by Means of Piezoelectric Dynamic Vibration Absorbers - Michele Tonan; Alberto Pasetto; Alberto Doria (Applied Sciences, 2024)
In this paper, the possibility of harvesting energy from the vibrations of a plate is analyzed. The harvester takes the form of a cantilever dynamic vibration absorber equipped with a piezoelectric layer and tuned by means of a tip mass to the first mode of vibration of the plate. A mathematical model of the coupled system composed of the plate and the harvester is presented. The validity of the proposed harvester is proved by means of simulations carried out with the modal expansions approach. Simulation results highlighting the effects of harvester tuning and location are presented as well. Then, the validity of the harvester is confirmed by experimental tests carried out both with a concentrated impulsive load and with a distributed pressure load. Simulations and experimental tests are performed on the cantilever piezoelectric dynamic vibration absorber and on the same piezoelectric layer directly bonded to the plate surface. Results show an improvement in terms of generated voltage when the proposed novel device is used in place of the simple layer.